2015
DOI: 10.1039/c4ta05332j
|View full text |Cite
|
Sign up to set email alerts
|

Robust superhydrophobic TiO2@fabrics for UV shielding, self-cleaning and oil–water separation

Abstract: Multifunctional robust TiO2@fabrics with special wettability demonstrated potential applications for excellent UV shielding, effective self-cleaning, efficient oil–water separation and microfluidic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
216
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(217 citation statements)
references
References 81 publications
1
216
0
Order By: Relevance
“…Durable superhydrophobic coatings have been reported recently, 26 such as acrylic polyurethane based coating, 27 textured surface obtained by chemical etching, 28,29 surfaces template from innately microstructured hydrogel matrix, 30 block-copolymer-based thin-film patterning, 31 combination of rodlike palygorskite and organosilanes via spray-coating, 32 fluorine-free polysiloxane/multiwalled carbon nanotubes, 33 titanium dioxide materials with special wettability, 34 or various coatings fabricated on fabrics/sponges/cotton. [35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion. 27,29,[41][42][43] Besides, the mechanical stability may be simply due to the fact that the coating thickness is too thick to be worn out completely to expose the substrate surface underneath the superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 99%
“…Durable superhydrophobic coatings have been reported recently, 26 such as acrylic polyurethane based coating, 27 textured surface obtained by chemical etching, 28,29 surfaces template from innately microstructured hydrogel matrix, 30 block-copolymer-based thin-film patterning, 31 combination of rodlike palygorskite and organosilanes via spray-coating, 32 fluorine-free polysiloxane/multiwalled carbon nanotubes, 33 titanium dioxide materials with special wettability, 34 or various coatings fabricated on fabrics/sponges/cotton. [35][36][37][38][39][40] However, most of the reported surfaces are not durable enough, as they can only resist abrasion against wipes, 28 fine sandpaper (e.g., 800, 1000, 2000 grid), mild droplets/sand impinging, 30,31 or were easily disabled after a short distance (i.e., less than 5 m) of abrasion. 27,29,[41][42][43] Besides, the mechanical stability may be simply due to the fact that the coating thickness is too thick to be worn out completely to expose the substrate surface underneath the superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ag NPs were also synthesized on fabric surface to achieve good color fastness, antimicrobial property and UV protection. 7 Yu et al found that multifunctional metal commingled yarns composed of antibacterial nylon/polyester/stainless steel wires could achieve good moisture wicking and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the smooth PDA coatings obtained by typical method can hardly form primary obvious hierarchical structure, thus with the following secondary reaction, only hydrophobic surfaces would be achieved [35]. Various nanoparticles including noble metal (Ag) [36], metallic oxide (Fe 3 O 4 ) [37], and silicon oxide [38] were incorporated through the catechol coordinate bonds and hydrogen bonds to create primary hierarchical structures on HNTs surfaces, however, this most-used approach suffered from a lot of disadvantages, such as high cost, time-consuming, and poor stability. Therefore, a direct way to control the roughness of PDA coatings without incorporation of nanoparticles was urgently needed.…”
Section: Preparation Process and Reaction Mechanismmentioning
confidence: 99%